2009
DOI: 10.1354/vp.08-vp-0150-w-fl
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic Ameloblastomas in Chinook Salmon (Oncorhynchus tshawytscha) of the Northwestern United States

Abstract: Abstract. Abnormal growths were observed on the lips and in the oral cavities of 2-and 3-year-old Chinook salmon (Oncorhynchus tshawytscha) maintained in one freshwater and one saltwater captive fish-rearing facility in the Columbia River (Pacific Northwest). Initially presenting as bilaterally symmetrical, red, irregular plaques on oral mucosal surfaces, the lesions developed progressively into large, disfiguring masses. Of the 502 natural parr collected for captive broodstock, 432 (86%) displayed these tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Studies on oral tumours in fish are very scarce (Schlumberger & Lucke 1948, Gopalakrishnan et al 2011, Vijayakumar et al 2014, although some spontaneous oral tumours have been reported (Honma et al 2003, Grim et al 2009, Coffee et al 2013, Videira et al 2015. Gopalakrishnan et al (2011) and Vijayakumar et al (2014) reported intra-oral sarcomas and compound odontomas in Sphyraena barracuda and S. jello in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on oral tumours in fish are very scarce (Schlumberger & Lucke 1948, Gopalakrishnan et al 2011, Vijayakumar et al 2014, although some spontaneous oral tumours have been reported (Honma et al 2003, Grim et al 2009, Coffee et al 2013, Videira et al 2015. Gopalakrishnan et al (2011) and Vijayakumar et al (2014) reported intra-oral sarcomas and compound odontomas in Sphyraena barracuda and S. jello in India.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, oral tumours (i.e. odontomas, ameloblastomas, papillomas and fibromas) have been reported in Melanogrammus aeglefinus (Thomas 1926), Oncorhynchus tsha wyt scha (Schlumberger & Katz 1956, Stolk 1957, Stock ley 1975, Grim et al 2009), Sparus aurata (Harshbarger 1974, Easa & Faisal 1987, Tautogolabrus adsphersus (Harsh barger 1974), Cyprinodon variegatus variegatus (Martineau et al 1990), Alcichthys elongatus (Honma et al 2003), Carcharias taurus, Prionace glauca (Boru cins ka et al 2004), Sphyraena barracuda (Gopalakrishnan et al 2011), Sander vitreus (Coffee et al 2013), Sphyraena jello (Vijayakumar et al 2014), Pterophyllum scalare (Videira et al 2015) and Carcharodon carcharias (Huveneers et al 2016). However, odontomas, myxomas and psammomatoid ossifying fibromas are rare tumours in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblastomas are formed strictly from the enamel organ, whereas odontomas produce the full gamut of tooth structures including enamel (from the epithelium) and dentin (from the ectomesenchyme). Ameloblastomas are reported in the veterinary literature, in dogs, cats, horses, cattle, rats, a llama, an alpaca, a black rat snake, and several species of fish (Britt et al 2005;Grim et al 2009;Comolli et al 2015). Given the local damage these tumors can inflict and their propensity to recur if not adequately treated, the current recommendation is surgical resection (Sham et al 2009).…”
Section: ò4mentioning
confidence: 99%
“…Association with human papillomavirus has been reported in people with ameloblastoma (Sham et al 2009), and polyomaviruses are used as a model for induction of ameloblastomas in mice (Stanley et al 1964). An epizootic of ameloblastomas was seen in salmon in which 100 nm particles morphologically consistent with a large icosahedral virus were seen that could not be further characterized (Grim et al 2009). There is limited evidence that herpesviruses may play a role in ameloblastoma induction; one study found small RNA encoded by Human herpesvirus 4 in 15% of ameloblastomas and none of the controls (Fujita et al 1997).…”
Section: ò4mentioning
confidence: 99%
“…6,7 In nonmammalian species, ameloblastomas have been characterized in captive-reared Chinook salmon ( Oncorhynchus tshawytscha ). 8…”
mentioning
confidence: 99%